A rare case of sudden death due to endomyocardial fibrosis in Italy: A differential diagnosis with other causes of restrictive cardiomyopathy. (January 2023) - Rossetti, Chiara; Belli, Giacomo; Franceschetti, Lorenzo; Restori, Mario; Braga, Paola; Garberi, Cesare; Picozzi, Mario; Birkhoff, Jutta Maria; Verzeletti, Andrea
Abstract: A 45-years-old Indonesian woman was admitted to the hospital with nausea, vomiting, abdominal pain and tachyarrhythmia. Atrial fibrillation was found at ECG, blood tests showed mild hepatic function alterations. Radiological exams showed bilateral pleural effusions, ascites, hepatomegaly. Systolic and diastolic functions of the left ventricle were found to be strongly compromised at US. Physical conditions and laboratory results worsened rapidly, followed by multi organ failure. Death occurred 28 hours after admission. An autopsy was performed to clarify the cause of death and investigated medical malpractice. External examination showed jaundice skin and at internal examination bilateral pleural and pericardial effusions, ascites, mild cardiomegaly, ventricular endocardial fibrosis, a thrombus in tight junction to the left ventricular wall and hepatic necrosis were observed. Histological investigations revealed a massive endomyocardial fibrosis, detected through Azan-Mallory and Verhoef-Van-Gieson stain, and confirmed the presence of hepatic and renal necrosis. Toxicological and microbiological investigations were negative. The cause of death was a global cardiac dysfunction caused by a restrictive cardiomyopathy in an Indonesian woman affected by an undiagnosed and asymptomatic endomyocardial fibrosis. In this case, autopsy and histopathological investigations were fundamental to diagnose an occult endomyocardial fibrosis, which is an idiopathic disorder of tropical and subtropical regions of the world. The not common incidence of this disease in our country and its unusual clinical onset were at first perceived as a medical malpractice from the relatives. Consequently, the clinical aspects of the case intertwine with the medicolegal implications concerning the undiagnosed disease and the causality with the patient's death. Highlights: Forensic pathology usually deals with unexpected diagnosis. Sudden death from endomyocardial fibrosis in Italy is a rare event. Histological analysis is needed for adequate post-mortem investigations. Differential diagnosis has to consider the geographical origin of the patient. Autopsy is crucial to investigate cases related to alleged medical claims.